Hubungan self-efficacy terhadap stress akademik pada mahasiswa - Annabilah, Fitri (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the relationship between self-efficacy and academic stress in university students through the literature study method. Self-efficacy is an individual’s belief in his or her ability to complete a task or overcome a particular challenge, while academic stress refers to the psychological pressure arising from academic demands. This study analyzed a number of relevant scientific articles to explore how self-efficacy levels affect the level of stress experienced by university students. The results of the literature review show that students with high levels of self-efficacy tend to be better able to manage academic pressure and less prone to stress, while students with low self-efficacy are more vulnerable to academic stress. This finding confirms the importance of developing self-efficacy in an effort to reduce stress levels in the college environment.